2007
DOI: 10.1007/s10856-007-3039-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel nanocrystalline hydroxyapatite paste and a solid hydroxyapatite ceramic for the treatment of critical size bone defects (CSD) in rabbits

Abstract: The purpose of our study was to test the effectiveness of Ostim nanocrystalline hydroxyapatite paste and Cerabone ceramic by treating a critical size bone defect (CSD) on the right foreleg of a white New Zealand rabbit. Evaluation was carried out by comparing four groups each with a different CSD filling: an only OSTIM bone filling, an only Cerabone filling, an OSTIM-Cerabone combination, and a control group with no filling of the CSD. The results of this study display a rapid and uniform bone ingrowth followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…For a number of clinical applications, Ostim® might be combined with other types of calcium orthophosphate bioceramics, e.g., with a HA bioceramic core (Cerabone®) [610,624] or with biphasic (β-TCP + HA) granules (BoneSaves®) [625]. Application of such combinations of a nanocrystalline Ostim® with the microcrystalline calcium orthophosphate bioceramics appeared to be an effective method for treatment of both tibia head compression fractures [610] and metaphyseal osseous volume defects in the metaphyseal spongiosa [624]. Besides, such combinations might be used for acetabular bone impaction grafting procedures [625].…”
Section: Bone Repairmentioning
confidence: 99%
“…For a number of clinical applications, Ostim® might be combined with other types of calcium orthophosphate bioceramics, e.g., with a HA bioceramic core (Cerabone®) [610,624] or with biphasic (β-TCP + HA) granules (BoneSaves®) [625]. Application of such combinations of a nanocrystalline Ostim® with the microcrystalline calcium orthophosphate bioceramics appeared to be an effective method for treatment of both tibia head compression fractures [610] and metaphyseal osseous volume defects in the metaphyseal spongiosa [624]. Besides, such combinations might be used for acetabular bone impaction grafting procedures [625].…”
Section: Bone Repairmentioning
confidence: 99%
“…Grigoryan et al described the rapid bone ingrowth at a low complication rate following the treatment of jaw defects with Ostim ® in dogs in 2000 [61]. Our own animal experiments dealing with the filling of critical size defects with Ostim in New Zealand white rabbits also resulted in swift and uniform bone ingrowth[62]. The results were further enhanced by the additional use of a sintered hydroxyapatite ceramic[62].…”
Section: Discussionmentioning
confidence: 99%
“…HA ceramics like Endobon Ò and Pro Osteon 500 Ò are fairly inert [39][40][41][42][43][44], whereas the HA cement Ostim Ò was shown to be biodegradable by osteoclastic activity [45][46][47][48][49][50]. After 1 year, 70% of the implanted material was resorbed in tibia bone of minipigs [50], but a recently published study found only minimal resorption of Ostim Ò after an implantation period of 12 weeks in rabbits femora [51].…”
Section: Biological Propertiesmentioning
confidence: 99%